До особливостей встановлення коефіцієнта шліфування при обробці ПНТМ - Пижов, Іван Миколайович; Федорович, Володимир Олексійович; Волошкіна, Ірина Віталіївна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Розглянуто питання, пов'язане з особливістю визначення такої фізичної характеристики процесу шліфування полікристалічних надтвердих матеріалів алмазними кругами на металічних та органічних зв'язках як коефіцієнт шліфування. Він уявляє собою відношення тангенціальної та нормальної складових сили різання при шліфуванні. Запропоновано визначати його з використанням ефективної складової тангенціальної складової сили різання. Її встановлення базується на основі використання явища пристосування процесу шліфування взагалі і її окремої складової-періодичності зміни в часі фізичних та технологічних показників обробки зокрема. Розкрита фізична сутність виникнення періодичності стосовно умов керованого процесу шліфування за пружною схемою і стосовно умов процесу шліфування ПНТМ алмазними кругами на органічних зв’язках в режимі самозаточування. У подальшому результати досліджень будуть сприяти удосконаленню процесів шліфування полікристалічних надтвердих матеріалів.

The questions related to the peculiarities of determining such a physical characteristic of the process of grinding polycrystalline superhard materials by diamond circles on metal and organic bonds as a coefficient of grinding are considered. It is the ratio of the tangential and normal components of the cutting force when grinding. It is proposed to determine it using the effective component of the tangential component of the cutting force. Its establishment is based on the use of the phenomenon of adaptation of the grinding process in general and its individual component, the periodicity of change in time of physical and technological indicators of processing in particular. The physical nature of the occurrence of the periodicity with respect to the conditions of the controlled grinding process according to the elastic scheme and to the conditions of the process of grinding polycrystalline superhard materials diamond circles on organic bonds in the self-sharpening mode is disclosed. It was established that when using the first process as a factor of forced influence on the state of the cutting surface of a circle it is necessary to choose the magnitude of intensity of electrophysical solution of the metal ligament of the diamond circle, and in the second transverse supply to the depth of processing. Recommendations regarding the choice of factors of forced influence are given. It is shown, that the peculiarity of the elastic treatment scheme is that the normal component of the cutting force is constant in time. Therefore, the change (increase or decrease) of the effective component of the tangential component of the grinding force leads to similar changes in the grinding coefficient and can clearly judge the effectiveness of the method or conditions of grinding that explores. In contrast to the elastic circuit grinding when working on a rigid scheme, both components (tangential and normal) grinding force, which are used to define the grinding coefficient, depend on the processing conditions. This fact should be considered when analyzing the obtained experimental data. In the future, research results will help to improve the grinding processes of polycrystalline superhard materials.
The peculiarities of setting the grinding coefficient in the processing of polycrystalline superhard materials
Keywords: самозаточування круга; сили різання; ефективна складова сили різання; періодичність процесу шліфування; self-sharpening of a circle; the cutting force; the effective component of the cutting force; the frequency of the grinding process